Using cue reactivity to screen medications for cocaine abuse: A test of amantadine hydrochloride - Robbins, Steven J.; Ehrman, Ronald N.; Childress, Anna Rose; O'Brien, Charles P. (Addictive behaviors, 1992)
The use of responding to drug-related stimuli as a dependent measure for studies of anticraving medications was assessed. Cocaine-dependent subjects receiving either amantadine hydrochloride, a putative anticraving agent, or placebo were exposed to drug-related cues prior to and 7 days after the initiation of the medication. Measurements of heart rate, skin resistance, skin temperature, and self-reported craving were taken during each stimulus session. Amantadine increased physiological reactivity to the drug-related cues compared to the placebo while having no effect on craving. Although the results discourage the use of amantadine as an anticraving medication, they do suggest that responses elicited by drug-related stimuli provide a valuable set of dependent measures for use in future medication trials of anticraving agents.